Outbreak of sexually transmitted, extensively drug-resistant Shigella sonnei in the UK, 2021–22: a descriptive epidemiological study. Issue 10 (October 2022) - Charles, Hannah; Prochazka, Mateo; Thorley, Katie; Crewdson, Adam; Greig, David R; Jenkins, Claire; Painset, Anais; Fifer, Helen; Browning, Lynda; Cabrey, Paul; Smith, Robert; Richardson, Daniel; et al.
Summary: Background: Shigellosis, traditionally a foodborne and waterborne infection, causes substantial morbidity globally. It is now a leading cause of sexually transmitted gastroenteritis among gay, bisexual, and other men who have sex with men (MSM). We describe an ongoing outbreak of extensively drug-resistant (XDR) Shigella sonnei in the UK. Methods: Routine laboratory surveillance (Second Generation Surveillance System, Gastrointestinal Data Warehouse) identified an exceedance of S sonnei clade 5 in England, first detected in September, 2021. Cases within this clade were subsequently reported from Scotland, Wales, and Northern Ireland. Confirmed cases in this outbreak were defined as individuals diagnosed with S sonnei clade 5 in the UK, with a specimen date between Sept 1, 2021, and Feb 9, 2022, who were genomically confirmed as part of a ten-single nucleotide polymorphism (SNP) linkage cluster. We used whole-genome sequencing with SNP typing to identify genomic clusters and antimicrobial-resistance determinants, analysing cases across the UK. We collected demographic, epidemiological, and clinical data from people infected with S sonnei clade 5 in England using questionnaires (standard and bespoke outbreak questionnaires). We used descriptive summary statistics to characterise cases. Findings: 72 cases (70 [97%] male, median age 34 years [IQR 27–39]) belonging to the ten-SNP single linkage cluster of S sonnei clade 5 were identified between Sept 4, 2021, and Feb 9, 2022. Isolates were predominantly XDR, with 66 (92%) of 72 harbouring bla CTX-M-27, a plasmid-mediated gene for production of extended-spectrum β-lactamases (ESBLs). Of 33 cases with clinical data, 19 (58%) received antibiotics and eight (24%) were hospitalised. 21 (78%) of 27 cases with completed bespoke outbreak questionnaires were HIV-negative MSM taking HIV pre-exposure prophylaxis (PrEP) who reported sexual contacts in the UK and Europe within the incubation period. Interpretation: We highlight the rapid dissemination of XDR ESBL-producing S sonnei in sexual networks of MSM. We recommend strengthening shigella testing where clinically indicated, antimicrobial-resistance surveillance, and integrated health promotion messaging among all MSM, including PrEP users, to reduce the burden of shigellosis. Funding: National Institute for Health Research Health Protection Research Unit in Gastrointestinal Infections at the University of Liverpool in partnership with the UK Health Security Agency.